2011
DOI: 10.1200/jco.2011.36.5908
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcomes of a Randomized Phase III Trial Comparing Adjuvant Chemotherapy With S-1 Versus Surgery Alone in Stage II or III Gastric Cancer

Abstract: On the basis of 5-year follow-up data, postoperative adjuvant therapy with S-1 was confirmed to improve overall survival and relapse-free survival in patients with stage II or III gastric cancer who had undergone D2 gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
1,016
7
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,223 publications
(1,069 citation statements)
references
References 25 publications
27
1,016
7
19
Order By: Relevance
“…We also saw an improvement in 5-year OS in patients who received 6 or >6 cycles of adjuvant chemotherapy compared to those who received <6 cycles adjuvant chemotherapy (45.0%, 42.9%, and 20.8%, respectively; p=0.001). Our findings of 5-year OS and RFS rates were lower than those of other studies from Asia, presumably due to differences in operation procedures (Sasako et al, 2011). In our follow-up study, patients with gastric cancer received D1 gastrectomy.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…We also saw an improvement in 5-year OS in patients who received 6 or >6 cycles of adjuvant chemotherapy compared to those who received <6 cycles adjuvant chemotherapy (45.0%, 42.9%, and 20.8%, respectively; p=0.001). Our findings of 5-year OS and RFS rates were lower than those of other studies from Asia, presumably due to differences in operation procedures (Sasako et al, 2011). In our follow-up study, patients with gastric cancer received D1 gastrectomy.…”
Section: Discussioncontrasting
confidence: 80%
“…Bang et al (2012) showed that 8 cycles of chemotherapy after D2 gastrectomy increased 3 year disease-free survival rates and lowered the risk of recurrence. Five-year outcomes of a randomized phase III trial by Sasako et al (2011) showed that patients with gastric cancer undergoing D2 gastrectomy could benefit from 8 cycles of postoperative adjuvant chemotherapy with S-1. The 5-year OS and RFS rates were 71.7% and 65.4%, respectively in the adjuvant chemotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the Japanese gastric cancer treatment guidelines 2014, patients with stage II and III GC, except for pT1 and pT3N0, are eligible for postoperative adjuvant chemotherapy for prevention of recurrence after surgery 13, 14. Oral administration of tegafur‐gimestat‐otastat potassium (S‐1) is standard practice for postoperative adjuvant chemotherapy 13, 14.…”
Section: Methodsmentioning
confidence: 99%
“…Oral administration of tegafur‐gimestat‐otastat potassium (S‐1) is standard practice for postoperative adjuvant chemotherapy 13, 14. On the basis of the Japanese gastric cancer treatment guidelines 2014, administration of S‐1 after curative resection has been performed at our institution 13, 14…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the surgery-alone arms, the 3-year overall survival (OS) of patients in the Asian CLASSIC trial was 78 %, compared to 41 % in the US INT-0116 trial, and 5-year OS in the ACTS-GC trial was 61 % compared to 23 % in the UK MAGIC trial [8][9][10][11]. Outcomes from trials conducted in Asian populations may therefore not be generalizable to those performed in Western populations and vice versa.…”
Section: How Geography and Surgery Impact On Treatment Choicementioning
confidence: 99%